2004
DOI: 10.1038/sj.embor.7400087
|View full text |Cite
|
Sign up to set email alerts
|

Involvement of the intermediate filament protein cytokeratin‐18 in actin pedestal formation during EPEC infection

Abstract: In the January 2004 issue, we published an error in Fig 4. The CK18 and CK8 labels that appeared in the two top left panels were added mistakenly, also the label in row 4 column 1 was incomplete. The figure should have been published as shown below.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
35
0

Year Published

2005
2005
2019
2019

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 22 publications
(36 citation statements)
references
References 0 publications
1
35
0
Order By: Relevance
“…Only those extracts prepared from wild‐type EPEC contained Tir. Cytokeratin 18 was included as a control because it has been shown to independently bind other 14‐3‐3 isoforms and Tir (Ku et al ., 1998; Batchelor et al ., 2004). A mouse monoclonal antibody directed against Tir was used to immunoprecipitate Tir and associated proteins in conjunction with immobilized protein A.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…Only those extracts prepared from wild‐type EPEC contained Tir. Cytokeratin 18 was included as a control because it has been shown to independently bind other 14‐3‐3 isoforms and Tir (Ku et al ., 1998; Batchelor et al ., 2004). A mouse monoclonal antibody directed against Tir was used to immunoprecipitate Tir and associated proteins in conjunction with immobilized protein A.…”
Section: Resultsmentioning
confidence: 99%
“…Although over the course of the experiment the disrupted HeLa cells did not demonstrate any observable growth defect, they were clearly deficient in their ability to mobilize actin for pedestal formation in response to EPEC. Recently it has been reported that EPEC infection may promote 14‐3‐3ζ interaction with cytokeratin 18 (Viswanathan et al ., 2004), an intermediate filament protein that also binds Tir (Batchelor et al ., 2004). The formation of functional 14‐3‐3 heterodimers in the regulation of the cytoskeletal remodelling required to form pedestal structure would seem a real possibility.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…It is widely accepted that the cytoskeleton and intercellular junctions are targeted by A/E pathogens (Spitz et al, 1995; Guttman et al, 2006a). Apart from the obvious alterations to the actin filament component of the cytoskeleton in pedestals, microtubules and intermediate filaments are also modified (Batchelor et al, 2004; Viswanathan et al, 2004b; Hardwidge et al, 2005; Tomson et al, 2005). Two studies have investigated the intermediate filament cytoskeleton and its modification during EPEC infection.…”
mentioning
confidence: 99%
“…Two studies have investigated the intermediate filament cytoskeleton and its modification during EPEC infection. Batchelor et al (2004) demonstrated that the intermediate filament protein cytokeratin‐18 is found in EPEC pedestals. Viswanathan et al (2004b) assessed the overall effects on cytokeratin‐18 during EPEC infection of T84 cells.…”
mentioning
confidence: 99%